The Low Prevalence of Overweight and Obesity in Czech Breastfed Infants and Young Children: An Anthropological Survey - Riedlová, Jitka; Paulová, Markéta; Vignerová, Jana; Brabec, Marek; Sedlak, Petr; Schneidrová, Dagmar (International journal of environmental research and public health, 2019)
The aim of this study is to evaluate the prevalence of overweight and obesity in a sample of children who were exclusively or predominantly breastfed for at least 6 months compared to Czech references that were constructed based on a representative sample of children, regardless of their mode of feeding. Between 2008 and 2011, a longitudinal study on the growth of breastfed infants was carried out in the Czech Republic. Forty-three GP pediatricians addressed parents at 18-month preventive examinations and collected data on the families' socio-economic conditions and the infants' feeding conditions. The children were measured (length, weight, and head circumference), and anthropometric measurements from 10 previous preventive examinations were obtained from the health records. Out of the collected 1775 questionnaires, 960 children were selected according to the criteria of the WHO Multicentre Growth Reference Study. For the purpose of this study, 799 children who were exclusively or predominantly breastfed for at least 6 months were selected. We found that the proportions of children who were classified as overweight (>90th percentile) or obese (>97th percentile) at 6, 12, and 18-month examinations were far below the proportions of the Czech references. An update of the Czech references and growth charts is highly recommended by GP pediatricians for the valid assessment of growth and nutritional status, including a screening of overweight and obesity in primary preventive health care.
Keywords: novorozenec; kojení; Infant, Newborn; nutriční stav; Infant; Humans; Longitudinal Studies; kojenec; ochranné faktory; growth charts; prevalence; Pediatric Obesity; Female; overweight; Protective Factors; lidé; Nutritional Status; vývoj dítěte; ženské pohlaví; longitudinální studie; Growth Charts; obezita dětí a dospívajících; Male; Child Development; Czech Republic; Prevalence; breastfed infants; růstové grafy; Breast Feeding; Česká republika; mužské pohlaví; obesity; primary health care